CONTACT INTEGRABLE EXTENSIONS OF SYMMETRY PSEUDO-GROUP AND COVERINGS FOR THE R-th DOUBLE MODIFIED DISPERSIONLESS KADOMTSEV-PETVIASHVILI EQUATION - O. I. Morozov; M. V. Pavlov (Научный вестник МГТУ ГА, 2016)
We find contact integrable extensions and coverings for the r-th double modified dispersionless Kadomtsev-Petviashvili law equation. One of the coverings provides a Bäcklund auto-transformation and a recursion operator for the equation under the study.